Android-based fashion terms digital dictionary application development (International Journal of Scientific Research and Management (IJSRM), 2022)
There is no digital dictionary application in the fashion sector. There are books for fashion terms that cannot be carried since they are printed. An Android-based digital dictionary application can be carried easily. Hence, this research developed a digital dictionary for fashion terms based on Android. This research was conducted using the ADDIE (Analysis, Development, Design, Implementation, and Evaluation) development model. The validity test from material experts, media experts, and trials results were declared feasible. Thus, the Android-based digital dictionary application for fashion terms was feasible and can be used for teaching purposes in the fashion area.